Exchange rate floor and central bank balance sheets: Simple spillover tests of the Swiss franc - Adrien Alvero; Andreas M. Fischer (Swiss National Bank, Study Center Gerzensee, 2016)
This paper examines spillover and spillback effects of unconventional monetary policies conducted by the European Central Bank (ECB) and Swiss National Bank (SNB) on the exchange rate's distribution. The empirical setup examines the price response of EURCHF risk reversal to a change in ECB and SNB balance sheets, with a distinction for the period of the minimum exchange rate (floor). The analysis finds only weak evidence of spillover effects from the ECB, while the spillback effect from the SNB balance sheet is robust during the floor period.
Keywords: E52; E58; F31; G15; 330; central bank balance sheets; spillovers and spillbacks; risk reversals; OLS regression